Gold Nanoparticles Electrodeposition Onto Thick Diazonium Film for Sensitive and Long-Lasting Hg(II) Trace Sensing - Fatma Fezai; Christelle Virolle; Yacine Kacimi; Brigitte Dustou; Dunya El Boutaybi; Childérick Séverac; Pierre Gros; Martine Meireles; David Evrard (International Journal of Electrochemistry)
A new electrochemical sensor devoted to Hg(II) trace determination was developed by tailoring a hybrid organic/inorganic interface using diazonium salts and gold nanoparticles (AuNPs). The AuNPs were electrodeposited for the very first time onto glassy carbon (GC) electrodes functionalized by thick (ca. 4 nm) diazonium films. The thickness of the organic films was obtained using atomic force microscopy (AFM) in scratching mode, while the AuNPs were characterized by field emission gun scanning electron microscopy (FEG-SEM). Each step of the functionalization process was studied by cyclic voltammetry using ferricyanide and ruthenium hexaammine as the redox probes. The as-prepared electrode was used for Hg(II) trace detection through square wave anodic stripping voltammetry (SWASV). A linear response was observed in the 1.0–9.9 nmol·L−1 range using a preconcentration time of 300 s, yielding a normalized sensitivity of 0.03 μA·L·nmol−1·min−1. The limit of detection (LOD) was determined to be as low as 300 pmol·L−1. The effect of major interfering metal cations on the sensor’s response was also investigated. In addition, the hybrid organic/inorganic interface strongly enhanced the lifetime of the sensor, this latter being extended up to 4 weeks.